Active recombinant Tol2 transposase for gene transfer and gene discovery applications. Issue 1 (December 2016) - Ni, Jun; Wangensteen, Kirk; Nelsen, David; Balciunas, Darius; Skuster, Kimberly; Urban, Mark; Ekker, Stephen
Abstract Background The revolutionary concept of "jumping genes" was conceived by McClintock in the late 1940s while studying theActivator/Dissociation (Ac/Ds ) system in maize. Transposable elements (TEs) represent the most abundant component of many eukaryotic genomes. Mobile elements are a driving force of eukaryotic genome evolution. McClintock'sAc, the autonomous element of theAc/Ds system, together withhobo fromDrosophila andTam3 from snapdragon define an ancient and diverse DNA transposon superfamily namedhAT. Other members of thehAT superfamily include the insect elementHermes andTol2 from medaka. In recent years, genetic tools derived from the 'cut' and 'paste'Tol2 DNA transposon have been widely used for genomic manipulation in zebrafish, mammals and in cells in vitro. Results We report the purification of a functional recombinantTol2 protein fromE.coli . We demonstrate here that following microinjection using a zebrafish embryo test system, purifiedTol2 transposase protein readily catalyzes gene transfer in both somatic and germline tissues in vivo. We show that purifiedTol2 transposase can promote both in vitro cutting and pasting in a defined system lacking other cellular factors. Notably, our analysis ofTol2 transposition in vitro reveals that the target site preference observed forTol2 in complex host genomes is maintained using a simpler target plasmid test system, indicating that the primary sequence might encode intrinsic cues for transposon integration. Conclusions This activeTol2 protein is an important new tool for diverse applications including gene discovery and molecular medicine, as well as for the biochemical analysis of transposition and regulation ofhAT transposon/genome interactions. The measurable but comparatively modest insertion site selection bias noted forTol2 is largely determined by the primary sequence encoded in the target sequence as assessed through studyingTol2 protein-mediated transposition in a cell-free system.